Higher risk of Achilles tendon ruptures at competition than training sites in female collegiate gymnasts - Muhlenhaupt, E.; Stauss, H. M. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Reportedly, 17.2% of collegiate female gymnasts experience Achilles tendon ruptures (ATRs). Cumulative microtraumas resulting in chronic tendinopathy/tendinitis may contribute to this high injury risk. We hypothesized that the risk of ATRs in female collegiate gymnasts increases with years of competitive gymnastics, that non-steroidal anti-inflammatory drug (NSAID) use is associated with less ATRs, and that the risk is larger during competition than training. METHODS: Female gymnasts from 78 USA collegiate teams completed a survey assessing the prevalence of ATRs, NSAID use, age at which competitive gymnastics started and age at which ATR occurred, and whether ATRs occurred during training or competition. RESULTS: Twenty-one of 103 gymnasts (20.4%, 95% CI: 13.6% to 29.4%) experienced ATRs. Eighteen of 21 ruptures (85.7%, 95% CI: 61.3% to 95.8%) occurred after more than ten years of competitive gymnastics (mean: 14.0±2.6 years, 95% CI: 12.8 to 15.2 years). ATRs occurred 0.08±0.01 (95% CI: 0.06 to 0.11) times per 1000 hours at training versus 1.85±0.11 (95% CI: 1.60 to 2.10) times per 1000 hours at competition (P<0.05). Prevalence of NSAID use was 27.6% (95% CI: 18.6% to 39.0%) in gymnasts without ATR but only 5.5% (95% CI: 0.6% to 35.5%, P=0.09) in gymnasts with ATR. Multiple regression analysis demonstrated a negative association between NSAID use and incidence of ATRs (P<0.05). CONCLUSIONS: Female collegiate gymnasts are at high risk for ATRs, especially after more than ten years of competitive gymnastics and during competition.